2023
DOI: 10.1002/jev2.12285
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial outer membrane vesicles induce a transcriptional shift in arabidopsis towards immune system activation leading to suppression of pathogen growth in planta

Abstract: Gram-negative bacteria form spherical blebs on their cell periphery, which later dissociate from the bacterial cell wall to form extracellular vesicles. These nano scale structures, known as outer membrane vesicles (OMVs), have been shown to promote infection and disease and can induce typical immune outputs in both mammal and plant hosts. To better understand the broad transcriptional change plants undergo following exposure to OMVs, we treated Arabidopsis thaliana (Arabidopsis) seedlings with OMVs purified f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Outer membrane vesicles (OMVs) purified from Xanthomonas campestris pv , a Gram-negative plant pathogenic bacterium, could induce significant transcriptional changes in Arabidopsis. This activation has involved the immune system and upregulation of related pathways including multiple immune receptors [ 60 ]. Compared to mammalian exosomes, microbial-derived exosomes offer greater convenience for engineering modifications.…”
Section: Overview Of the Exosomesmentioning
confidence: 99%
“…Outer membrane vesicles (OMVs) purified from Xanthomonas campestris pv , a Gram-negative plant pathogenic bacterium, could induce significant transcriptional changes in Arabidopsis. This activation has involved the immune system and upregulation of related pathways including multiple immune receptors [ 60 ]. Compared to mammalian exosomes, microbial-derived exosomes offer greater convenience for engineering modifications.…”
Section: Overview Of the Exosomesmentioning
confidence: 99%
“…Campestris ( Xcc ), and Xoo and virulence factors purified from these EVs have been shown to trigger immune responses in plants, including callose deposition, the alkalinization of the medium, increased transcription of pattern recognition receptors, the activation of Mitogen-Activated Protein Kinase (MAPK), and the release of reactive oxygen species [ 21 , 22 ]. Alterations in crucial receptors like the plant elongation factor receptor (EFR), flagellin receptor (FLS2), or brassinosteroid-insensitive 1–associated kinase (BAK1) co-receptor had minimal effect on the immune priming ability of Xcc EVs [ 86 ]. These findings suggest that Xcc EVs elicit a widespread transcriptional shift in Arabidopsis , stimulating the activation of multiple immune pathways.…”
Section: Role Of Evs and Srna In Plant–microbe Interactionmentioning
confidence: 99%
“…Xcc EVs were shown to induce the expression of multiple WRKY transcription factors. This transcriptional modulation holds promise for enhancing the plant’s defense mechanisms against bacterial infections [ 86 ]. Tran et al [ 87 ] elucidated that the structured lipid composition of EVs enables direct interaction and integration of Xcc EVs into the Arabidopsis plasma membrane (PM), thereby enhancing its lipid organization.…”
Section: Role Of Evs and Srna In Plant–microbe Interactionmentioning
confidence: 99%
“…3 Other studies demonstrated a similar phenomena for Xanthomonas campestris and X. oryzae OMVs, which inhibited the growth of Arabidopsis thaliana. 116,117 Other nonplant associated bacteria P. aeruginosa, S. aureus, and enterotoxigenic E. coli also induced plant immune responses, albeit to different extents. 3 OMVs and plants more thoroughly elsewhere.…”
Section: Functions Of Evs Asmentioning
confidence: 99%
“…For instance, Samuel et al and An et al discuss fungal–plant interactions: how sometimes vesicular structures aid in the dissemination of fungal pathogens but also how similar structures can induce immune responses to combat the growth of harmful fungi on plants. , More recently, McMillan et al demonstrated that OMVs from P. syringae and P. fluorescens can elicit protective plant immune responses . Other studies demonstrated a similar phenomena for Xanthomonas campestris and X. oryzae OMVs, which inhibited the growth of Arabidopsis thaliana . , Other nonplant associated bacteria P. aeruginosa, S. aureus , and enterotoxigenic E. coli also induced plant immune responses, albeit to different extents . McMillan et al and Bahar et al further suggest that OMV-associated protein may not be the primary category of molecules that stimulates a response preventing plant infection.…”
Section: Extracellular Vesicles As Functional Colloids In the Environ...mentioning
confidence: 99%